أثر هيكلة الملكية كميكانيزم داخلي لحوكمة المؤسسات على أداء البنوك التجارية - رقية, د. حساني; أمال, أ.سكــــور (Recherches économiques et managériales, 2015)
الملخص : تهدف هذه الورقة البحثية إلى دراسة هيكلة الملكية كميكانيزم داخلي للحوكمة من حيث دورها كأداة لتفعيل الرقابة على الإدارة وأثرها على الأداء في البنوك التجارية ، فحسب نظرية الوكالة تؤثر هيكلة الملكية على أداء المؤسسات عبر عنصرين هما : تركز رأس المال و طبيعة المساهمين .و تم التطرق في هذا البحث إلى وجهات نظر مفكرين اقتصاديين و دراسات أكاديمية و نظريات تخص علاقة هيكلة الملكية بالأداء  في المؤسسات الاقتصادية بصفة عامة و البنوك التجارية بصفة خاصة.    الكلمات المفتاحية: هيكلة الملكية، نظرية الوكالة، حوكمة المؤسسات، الرقابة على المسيرين، الأداء في المؤسسات . Abstract  : This research aims to examine ownership structure as an internal mechanism of corporate governance, regarding to its role as a tool of management control on one hand and its impact on commercial banks performance on other hand.  Accordingly, the agency theory recognize that ownership structure of a firm influences on its performance throw two of its components: the capital concentration and the nature of shareholders. This paper dealt with theories and academic researches concerning the relationship between ownership structure and firm performance in general and banks performance in particularly.  Key Words  :Ownership structure , agency theory , corporate governance, control management , corporate performanc